Pengaruh jenis substrat berbeda dalam proses penggemukan kepiting bakau (Scylla serrata) di CV. Elitism NTT, Kelurahan Oesapa Barat, Kecamatan Kelapa Lima, Kota Kupang - Njuruhapa, Rivaldo Alvadio; Linggi, Yulianus; Liufeto, Franchy Ch (Jurnal Aquatik, 2024)
This research aims to determine how different types of substrate affect the duration of growth during the fattening phase of mud crabs (Scylla serrata). Carried out for one month at CV.Elitsm NTT, in West Oesapa Village, Kelapa Lima District, Kupang City. Randomized Block Design (RAK) was used in this research which consisted of four treatments and replications. The treatments given include: Muddy substrate with mangrove leaves (A), Muddy substrate (B), Mangrove leaf substrate (C), and Without substrate (D). The findings show that the use of muddy substrates with mangrove leaves provides the most beneficial results in accelerating the growth period during the mud crab fattening process. In 14 days after cultivation, the mud crabs were already developing well. Keywords: Mangrove crab (Scylla serrata), fattening and substrate.